Effect of Organics on Breaking of Seed Dormancy in Cardamom - SHANTAPPA TIRAKANNANAVAR; RANJITHA HB; RATNAKAR M SHET (Seed Research, 2026)
The experiments was carried out in the Department of Crop Improvement and Biotechnology, College of Horticulture, Sirsi, Uttara Kannada district located in hilly zone (Zone-9) of Karnataka during September - January of 2016-17. The experiment consist of eight treatments viz., T1: Cow urine @ 50% dilution for 30 min, T2: Cow dung slurry @ 50% dilution for 30 min, T3: Hot water treatment at 50oC for 2 min, T4: Vermi wash @ 50% dilution for 60 min,T5: Panchagavya @ 5% for 60 min, T6: Beejamruta @ 3% for 60 min,T7: Water soaking for 12 hours and T8: Nitric acid 25% for 10 min (Control). The germination per cent was recorded significantly highest in nitric acid treatment (80.00) at 60 days after sowing. The highest seedling quality parameters viz., root length (2.36 cm), shoot length (6.48 cm) seedling length (8.85 cm), seedling fresh weight (55.0 mg), seedling dry weight about (6.20 mg), seedling vigour index-I (707) and seedling vigour index-II (496) in nitric acid treatment.